2020
DOI: 10.2174/1389200221666200514081947
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolites in the Treatment of Diabetes Mellitus: A Paradigm Shift

Abstract: : Diabetes mellitus (DM) is a chronic, polygenic and non-infectious group of diseases that occurs due to insulin resistance or its low production by pancreas and is also associated with lifelong damage, dysfunction and collapse of various organs. Management of diabetes is quite complex having many bodily and emotional complications and warrants efficient measures for prevention and control of the same. As per the estimates of current and future diabetes prevalence around 425 million people were diabetic in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 153 publications
0
5
0
Order By: Relevance
“…Akt activates the glucose transporter translocation to the cellular membrane (GLUT-4) and triggers the phosphorylation of glycogen synthase kinase 3 (GSK3), which leads to stimulation of glycogen synthesis in liver and skeletal muscle and downregulation of PEPCK (phosphoenolpyruvate carboxykinase) and G6Pase (glucose-6- phosphatase) gene expression [ 24 ]. However, in a diabetic state, these pathways are not blocked because insulin is unable to adequately regulate the gene expression and function of PEPCK and G6Pase, leading to excessive hepatic glucose production through gluconeogenesis and glycogenolysis [ 9 , 16 ]. In addition, the activation of the Akt system leads to protein synthesis through the activation of the mechanistic target of rapamycin complex 1 (mTORC1), cell survival by the suppression of various pro-apoptotic molecules, mainly of the FOXO (forkhead box O) family of transcription factors ( Figure 4 ) [ 27 ].…”
Section: Insulin Signal Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akt activates the glucose transporter translocation to the cellular membrane (GLUT-4) and triggers the phosphorylation of glycogen synthase kinase 3 (GSK3), which leads to stimulation of glycogen synthesis in liver and skeletal muscle and downregulation of PEPCK (phosphoenolpyruvate carboxykinase) and G6Pase (glucose-6- phosphatase) gene expression [ 24 ]. However, in a diabetic state, these pathways are not blocked because insulin is unable to adequately regulate the gene expression and function of PEPCK and G6Pase, leading to excessive hepatic glucose production through gluconeogenesis and glycogenolysis [ 9 , 16 ]. In addition, the activation of the Akt system leads to protein synthesis through the activation of the mechanistic target of rapamycin complex 1 (mTORC1), cell survival by the suppression of various pro-apoptotic molecules, mainly of the FOXO (forkhead box O) family of transcription factors ( Figure 4 ) [ 27 ].…”
Section: Insulin Signal Transductionmentioning
confidence: 99%
“…Published research has proven that several secondary metabolites demonstrate hypoglycemic activity in vivo and in vitro, and usually, they affect multiple targets, proteins and enzymes. Alkaloids, phenols, anthocyanin, flavonoids, saponins, tannins, terpenes and coumarins were found to elicit a significant influence on diabetes [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that small molecule metabolite-based metabolomics can be further used to identify the active compounds and targets, which develop new therapies. 712 715 …”
Section: Efficacy Evaluationmentioning
confidence: 99%
“…Polyphenols can modulate carbohydrate metabolism, decrease hyperglycemia and control insulin resistance, increase lipid metabolism, optimize oxidative stress and inflammatory processes, inhibit α-glucosidase and α-amylase in the digestive tract. Also, polyphenols may modulate glucose uptake and expression of glucose transporters; stimulate insulin secretion and pancreatic β-cell proliferation [44][45][46][47] . Although pancreatic αamylase is an important enzyme that breaks down dietary long chain carbohydrates, still αglucosidase is a concluding enzyme that acts on shorter starch chains and disaccharides to produce glucose.…”
Section: Martmentioning
confidence: 99%